La ira del fuego - Mankell, Henning, 1948-2015; Giménez, Mayte; Sánchez, Pontus; Mankell, Henning, 1948-2015. (Madrid : Ediciones Siruela, 2011)
Sofia, who lost her legs as a child, is now grown up with children in Mozambique, but when she discovers that Armando, the father of her children, is cheating on her, she leaves him, igniting his terrible rage.
Online resource; title from ePub title page (Digitalia, viewed March 25, 2016)
Keywords: People with disabilities -- Juvenile fiction; Adultery -- Juvenile fiction; Families -- Juvenile fiction; Women -- Mozambique -- Social conditions -- Juvenile fiction; Mozambique -- Juvenile fiction; Electronic books